Mind wandering during hypertext reading: The impact of hyperlink structure on reading comprehension and attention - Teresa Schurer; Bertram Opitz; Torsten Schubert (Acta Psychologica, 2023)
Online reading is becoming more and more popular in learning and teaching environments. However, little is known about characteristics of hypertexts that influence on reading comprehension and attention. Some previous studies have suggested that attention failures also referred to as mind wandering (MW) occur whenever the available resources of the reader (e.g., working memory capacity; WMC) do not match the task demands (e.g., text difficulty). This study aims to investigate the effect of restructuring a linear text into different hypertext types by means of hyperlinks on MW in a cognitively demanding task like reading. We hypothesized that participants exposed to a difficult to read hypertext with networked structure engage more in task-unrelated thoughts (TUTs) compared to participants asked to read a difficult but hierarchically organized hypertext. 90 participants read either an easy or difficult version of the same unfamiliar hypertext with either a hierarchical or networked structure and with embedded thought probes. Reading comprehension and WMC measures followed. As expected, participants reading the difficult (to read) hypertext with networked link structure showed significantly more TUTs than participants reading the hierarchical link structure hypertext. In addition, readers with a low-WMC showed significantly more TUTs while reading a demanding hypertext regardless of its structure. These findings are in line with the view that mind wandering occurs if available resources do not match with task demands, and thus deepen assumptions about hyperlinks as new cohesive devices.